Pengaruh Beban Kerja Dan Manajemen Waktu Terhadap Efektivitas Kerja Karyawan Di Perumda Tirta Hidayah Kota Bengkulu - Lestari, Elis; Arini, Eti (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
The aim of the research is to determine the effect of workload and time management on employee work effectiveness. The research was carried out at the Head Office of the Regional Public Company (Perumda) Tirta Hidayah, Bengkulu City from November-December 2023. Respondents were 154 employees at the head office, it was found that 125 respondents participated after data collection via questionnaires. Data analysis uses multiple linear regression models. The research results showed that workload and work effectiveness had a negative effect. This explains that an increase in load will be followed by a decrease in work effectiveness. Time management and work effectiveness have a positive effect. This explains that an increase in time management will be followed by an increase in work effectiveness. Workload and time management on work effectiveness are significant. This explains that an increase in workload and time management will also be accompanied by an increase or decrease in work effectiveness.